2016
DOI: 10.1093/nar/gkw891
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants for CRISPR RNA maturation in the Cas10–Csm complex and roles for non-Cas nucleases

Abstract: CRISPR–Cas (Clustered regularly interspaced short palindromic repeats-CRISPR-associated proteins) is a prokaryotic immune system that destroys foreign nucleic acids in a sequence-specific manner using Cas nucleases guided by short RNAs (crRNAs). Staphylococcus epidermidis harbours a Type III-A CRISPR–Cas system that encodes the Cas10–Csm interference complex and crRNAs that are subjected to multiple processing steps. The final step, called maturation, involves a concerted effort between Csm3, a ruler protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 59 publications
5
70
0
Order By: Relevance
“…Similarly, Staphylococcus epidermidis (type III-A) has crRNAs that are 37, 43, and 72 nt in length (50). Walker et al (28) reported that 39 trimming of crRNAs in the type III-A S. epidermidis (Csm) complex is catalyzed by a trans-acting non-Cas nuclease, probably polyribonucleotide phosphorylase. However, mature crRNAs detected here in the M. tuberculosis system were of uniform size (;71 nt; Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Staphylococcus epidermidis (type III-A) has crRNAs that are 37, 43, and 72 nt in length (50). Walker et al (28) reported that 39 trimming of crRNAs in the type III-A S. epidermidis (Csm) complex is catalyzed by a trans-acting non-Cas nuclease, probably polyribonucleotide phosphorylase. However, mature crRNAs detected here in the M. tuberculosis system were of uniform size (;71 nt; Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that crRNA biogenesis depends critically on the activity of the Cas6 superfamily of endonucleases in type I and III CRISPR/Cas systems (6). In type III-A systems, Cas6 typically cleaves pre-crRNA to generate intermediate crRNAs that are then incorporated into the crRNP complex where the 39 end sequences may be trimmed by polyribonucleotide phosphorylase (28). Here, to verify that Cas6 is involved in crRNA processing in M. tuberculosis as in other species, we constructed a Cas6 deletion mutant (Dcas6); as expected, crRNA generation was not detected (Supplemental Fig.…”
Section: Mature Crrna Processing In M Tuberculosis Is a Cas6 Metal-imentioning
confidence: 99%
“…The overexpression and purification of recombinant CRISPR-associated proteins from Escherichia coli (both the Cas10-Csm complex and individual subunits) followed by in vitro biochemical assays have revealed important insights into their functions (Hatoum-Aslan et al ., 2013; Samai et al ., 2015; Walker et al ., 2016). However, such assays fail to 1) recover information about protein function and stability in the native cellular environment, and 2) identify biologically relevant binding partners that are not a part of the core Cas10-Csm complex.…”
Section: Introductionmentioning
confidence: 99%
“…However, such assays fail to 1) recover information about protein function and stability in the native cellular environment, and 2) identify biologically relevant binding partners that are not a part of the core Cas10-Csm complex. Indeed, purification of Cas10-Csm from its native S. epidermidis background has yielded additional insights into the genetic requirements for complex stability and function, crRNA processing, and non-Cas binding partners that might play a role in the CRISPR-Cas pathway (Hatoum-Aslan et al ., 2013 and 2014; Walker et al ., 2016). Here, we provide a detailed protocol for the purification of Cas10-Csm from S. epidermidis or S. aureus strains bearing the Type III-A CRISPR-Cas system on a plasmid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation